Lithium-sulfur battery positive electrode material, positive electrode plate, and preparation method and application thereof

By using zwitterionic polymers as binders in lithium-sulfur batteries, the transformation of its structural electrical properties can effectively adsorb lithium polysulfide, which solves the problem of lithium polysulfide "shuttle effect" in lithium-sulfur batteries and improves the efficiency and stability of the battery.

CN119905563APending Publication Date: 2025-04-29UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510097599.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing lithium-sulfur battery technology is difficult to effectively suppress the "shuttle effect" of lithium polysulfide, resulting in low battery coulomb efficiency and short cycle life.

Method used

Zwitterionic polymers are used as the binder for the sulfur positive electrode system. Through the mutual conversion of its structural electrical properties, lithium polysulfide (Li2Sx) neutral molecules and Sx-anions are efficiently adsorbed during the charging and discharging of lithium sulfur batteries.

Benefits of technology

It effectively suppresses the "shuttle effect" of lithium polysulfide, improves the Coulomb efficiency and cycle stability of lithium sulfur batteries, and improves the utilization rate and rate performance of sulfur.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905563A_ABST
    Figure CN119905563A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-sulfur battery positive electrode material, a positive electrode plate and a preparation method and application thereof, and belongs to the technical field of lithium-sulfur batteries. The lithium-sulfur battery positive electrode material comprises a sulfur positive electrode active substance, a conductive agent and a self-adaptive adhesive, wherein the self-adaptive adhesive is a zwitterionic polymer; the lithium-sulfur battery positive plate comprises a pole piece carrier and an active layer coated on the pole piece carrier, wherein the active layer comprises the lithium-sulfur battery positive electrode material disclosed by the invention. According to the present invention, the zwitterionic polymer is adopted as the binder of the sulfur positive electrode system, such that the efficient adsorption of the Li2Sx neutral molecule and the Sx-anion can be achieved during the battery charging and discharging process based on the mutual conversion of the structure electrical property of the zwitterionic polymer so as to completely inhibit the shuttle effect of the battery; and the zwitterionic polymer has a high-adaptability molecular structure and contains a large number of active groups, so that the completeness of the electrode in the charge-discharge cycle can be ensured, and the cycle stability can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and in particular relates to a lithium-sulfur battery positive electrode material, a positive electrode sheet, and a preparation method and application thereof. Background Art

[0002] Lithium-sulfur batteries (LSBs) are considered to be the most promising next-generation energy storage devices due to their high theoretical energy density, abundant sulfur reserves, low price, and environmental friendliness. However, the discharge intermediate product lithium polysulfide (Li2S x , x = 4-8) dissolution and migration bring about the "shuttle effect", which leads to defects such as low Coulomb efficiency and short cycle life of the battery, greatly limiting its commercial application. Therefore, how to reduce the "shuttle effect" of lithium polysulfide has become a research hotspot in lithium-sulfur batteries.

[0003] Limiting and sealing lithium polysulfide on the positive electrode side is the most direct and effective strategy to solve the "shuttle effect". To this end, the relevant technology designs the positive electrode through high specific surface area porous structure carbon materials (such as graphene, carbon nanotubes) to limit and capture lithium polysulfide, but the surface of non-polar carbon materials and polar lithium polysulfide cannot form a stable chemical reaction, and it is difficult to effectively suppress the "shuttle effect" for a long time. Therefore, the relevant technology has developed and designed an improved strategy to adsorb lithium polysulfide by using the chemical interaction formed by polar metal oxides and lithium polysulfide.

[0004] However, insulating metal oxides will hinder the transmission of electrons and lithium ions, reduce the utilization rate and rate performance of sulfur, and lead to unsatisfactory practical application results. More importantly, lithium polysulfide will produce obvious ionization when dissolved in electrolyte, making lithium polysulfide in the electrolyte in addition to lithium polysulfide (Li2S x ) In addition to the neutral molecular form, there is also a considerable amount of S x - The existing lithium-sulfur cathode system generally ignores the simultaneous adsorption of dynamically changing complex intermediates, resulting in the inability to fully suppress the "shuttle effect" of lithium polysulfide. Therefore, it is necessary to design and prepare a lithium polysulfide (Li2S) cathode system that can simultaneously adsorb lithium polysulfide. x ) Neutral molecules and S x - The anionic sulfur cathode system is expected to further suppress the "shuttle effect". Summary of the invention

[0005] The present application discloses a lithium-sulfur battery positive electrode material, a positive electrode sheet, a preparation method and an application thereof, aiming to solve the problems of low sulfur utilization rate, poor rate performance and inability to efficiently adsorb lithium polysulfide (Li2S) in the prior art strategy for suppressing the "shuttle effect" as described in the background above. x ) Neutral molecules and S x -Technical issues with anions.

[0006] In order to achieve the above objectives, the technical solution provided by this application is:

[0007] The first aspect of the present application provides a lithium-sulfur battery positive electrode material. The lithium-sulfur battery positive electrode material of the present application comprises a sulfur positive electrode active material;

[0008] a conductive agent; and,

[0009] Adaptive adhesives;

[0010] Wherein, the adaptive adhesive is a zwitterionic polymer.

[0011] In a preferred embodiment, the zwitterionic polymer comprises sulfonated chitosan or sulfonated polyethyleneimine.

[0012] In a preferred embodiment, the conductive agent comprises 0-50 mass % of a first conductive agent and 50-100 mass % of a second conductive agent;

[0013] Wherein, the first conductive agent is conductive carbon black;

[0014] The second conductive agent includes any one of carboxylated carbon nanotubes, carboxylated graphene, carboxylated conductive carbon black, or carboxylated conductive polymers.

[0015] In a preferred embodiment, the sulfur positive electrode active material comprises elemental sulfur or a sulfur-based conductive polymer.

[0016] In a preferred embodiment, the lithium-sulfur battery positive electrode material comprises:

[0017] 60-80% by mass of sulfur positive electrode active material; 10-38% by mass of conductive agent;

[0018] and, 2-10 mass % of an adaptive binder;

[0019] The sum of the mass percentages of each component is 100%.

[0020] The second aspect of the present application provides a positive electrode sheet for a lithium-sulfur battery. The positive electrode sheet for a lithium-sulfur battery of the present application comprises:

[0021] a pole piece carrier; and

[0022] An active layer coated on the pole piece carrier;

[0023] The active layer comprises the lithium-sulfur battery positive electrode material of the present application.

[0024] In a preferred embodiment, the pole piece carrier comprises a carbon aluminum foil current collector or a carbon cloth.

[0025] The third aspect of the present application provides a method for preparing a positive electrode sheet for a lithium-sulfur battery. The preparation method of the present application comprises the following steps:

[0026] Providing a dispersion containing a sulfur positive electrode active material and a conductive agent;

[0027] Adding an adaptive binder to the dispersion and mixing well to obtain a sulfur positive electrode slurry;

[0028] The sulfur positive electrode slurry is coated on a pole piece carrier and dried to obtain a lithium-sulfur battery positive electrode piece.

[0029] A fourth aspect of the present application provides a lithium-sulfur battery, which comprises the lithium-sulfur battery positive electrode sheet of the present application.

[0030] A fifth aspect of the present application provides an electrical device, which comprises the lithium-sulfur battery of the present application.

[0031] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application at least include:

[0032] The lithium-sulfur battery positive electrode material provided in the present application introduces a zwitterionic polymer as a binder of the sulfur positive electrode system. Since the ionic chain of the zwitterionic polymer has the ability to separate and convert the bonding state under the driving effect of the positive and negative charge distribution, it can show different charge centers during the battery charging and discharging process to achieve the effect of lithium polysulfide (Li2S x ) Neutral molecules and S x 2- Efficient adsorption of anions. Specifically, the positive charge center of the zwitterionic polymer in an electrically neutral state can be wrapped by the anionic groups of the ionic side chains during the battery discharge process and form a curled structure similar to a clenched fist. This structure can shield the positive charge center, making the zwitterionic polymer exhibit obvious electronegativity and show efficient adsorption of lithium polysulfide molecules; when the battery is charged, the zwitterionic polymer is in a cationic state, making the fist-like curled structure transform into a linear structure, the shielding effect disappears and the positive charge center is released, making the zwitterionic polymer exhibit obvious electropositivity. At the same time, the polysulfide compounds are adsorbed with the free Li + The migration of S x 2- The negative charge center of the group is released, so that it can be efficiently adsorbed by the zwitterionic polymer with positive charge. Therefore, the present application uses the zwitterionic polymer as the binder of the sulfur positive electrode system, which can not only realize the mutual transformation of the structural charge of the zwitterionic polymer during the battery charging and discharging process, but also realize the adsorption of lithium polysulfide (Li2S x ) Neutral molecules and S x -The efficient adsorption of anions fully suppresses the "shuttle effect" of lithium-sulfur batteries. The active groups and highly adaptable molecular structures contained in zwitterionic polymers can promote contact and enhance adhesion between active materials, conductive agents and current collectors, so that the sulfur positive electrode sheet has a stable 3D cross-linked structure, ensuring the integrity of the electrode during the charge and discharge cycle, allowing the battery to maintain efficient electron and ion transmission, and greatly improving the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 The infrared spectrum of sulfonated chitosan provided in the examples of the present application;

[0035] Figure 2 The discharge curve and coulombic efficiency test of the Li-S full battery prepared based on LSBs-PP1 provided in the embodiment of the present application;

[0036] Figure 3 The specific capacity-voltage diagram of the Li-S button full battery manufactured based on sulfonated chitosan with different sulfonation degrees provided in the examples of the present application;

[0037] Figure 4 Surface SEM image of the lithium-sulfur battery positive electrode sheet LSBs-PP2 provided in the embodiment of the present application;

[0038] Figure 5 A cycle performance diagram of a Li-S soft pack battery provided in an embodiment of the present application;

[0039] Figure 6 This is a lighting diagram of the Li-S soft pack battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0041] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the single symbol " / " means "or".

[0042] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can represent any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0043] In the following description of this embodiment, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.

[0044] In the following description of the present embodiment, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any stated value or intermediate value in the stated range and any other stated value or intermediate value in the stated range is also included in the present embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.

[0045] Unless otherwise stated, the technical / scientific terms used in the present embodiment have the same meanings as those generally understood by those skilled in the art to which the present application belongs. Although the present application only describes preferred methods and materials, any similar or equivalent methods and materials may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.

[0046] In a first aspect, an embodiment of the present application provides a lithium-sulfur battery positive electrode material, the raw material components of which preferably include a sulfur positive electrode active material, a conductive agent and an adaptive binder;

[0047] Wherein, the adaptive adhesive is a zwitterionic polymer.

[0048] In the present embodiment, a zwitterionic polymer is used as a binder for the sulfur positive electrode system. Since the ionic chains of the zwitterionic polymer have the ability to separate and convert between bonding states under the driving force of positive and negative charge distribution, different charge centers can be displayed during the battery charging and discharging process to achieve the effect of lithium polysulfide (Li2S x ) Neutral molecules and S x 2- Efficient adsorption of anions. Specifically, the positive charge center of the zwitterionic polymer in an electrically neutral state can be wrapped by the anionic groups of the ionic side chains during the battery discharge process and form a curled structure similar to a clenched fist. This structure can shield the positive charge center, making the zwitterionic polymer exhibit obvious electronegativity and show efficient adsorption of lithium polysulfide molecules; when the battery is charged, the zwitterionic polymer is in a cationic state, making the fist-like curled structure transform into a linear structure, the shielding effect disappears and the positive charge center is released, making the zwitterionic polymer exhibit obvious electropositivity. At the same time, the polysulfide compounds are adsorbed with the free Li + The migration of S x 2- The negative charge center of the group is released, so that it can be efficiently adsorbed by the zwitterionic polymer with positive charge. Therefore, the present application uses the zwitterionic polymer as the binder of the sulfur positive electrode system, which can not only realize the mutual transformation of the structural charge of the zwitterionic polymer during the battery charging and discharging process, but also realize the adsorption of lithium polysulfide (Li2S x ) Neutral molecules and S x - The efficient adsorption of anions fully suppresses the "shuttle effect" of lithium-sulfur batteries. The active groups and highly adaptable molecular structures contained in zwitterionic polymers can promote contact and enhance adhesion between active materials, conductive agents and current collectors, giving the sulfur positive electrode a stable 3D cross-linked structure, ensuring the integrity of the electrode during the charge and discharge cycle, allowing the battery to maintain effective electron and ion transmission, and greatly improving the cycle stability.

[0049] According to the lithium-sulfur battery positive electrode material disclosed in the present application, the zwitterionic polymer preferably comprises sulfonated chitosan or sulfonated polyethyleneimine, more preferably sulfonated chitosan. Among them, the sulfonated chitosan molecular chain contains an amino cation center and a sulfonic acid anion center, which can be assembled into different structural electrical properties under the driving effect of positive and negative charge distribution, thereby efficiently adsorbing lithium polysulfide (Li2S) during the charge and discharge process of the lithium-sulfur battery. x ) Neutral molecules and S x - anions, thereby further inhibiting the shuttle effect of lithium polysulfide.

[0050] It should be noted that the present application does not specifically limit the specific sources of the sulfonated chitosan and sulfonated polyethyleneimine, which can be purchased from the market or synthesized by a sulfonation method known in the art, specifically based on the preparation of a zwitterionic polymer containing a sulfonic acid group. Among them, the present application embodiment provides an optional sulfonation method using sulfonated chitosan as an example, preferably comprising:

[0051] Chitosan is swelled in water, and a sulfonation reagent is added to the obtained chitosan solution to carry out a sulfonation reaction. The obtained product is then dialyzed for purification and freeze-dried to obtain sulfonated chitosan.

[0052] It should be noted that the present application does not specifically limit the type of sulfonating agent, which is based on the ability to provide sulfonated groups. Specifically, the sulfonating agent can be a common compound containing sulfonate groups such as 1,3-propane sultone, 1,4-butane sultone, and chlorosulfonic acid. At the same time, the amount of sulfonating agent added is preferably 40-90wt% of the mass of chitosan, the sulfonation reaction temperature is 30-60°C, and the reaction time is 4-8h.

[0053] It should be noted that the present application does not specifically limit the molecular weight and deacetylation degree of chitosan, and is based on the preparation of zwitterionic polymers that meet the adhesive requirements; the present application does not specifically limit the post-treatment of dialysis purification and freeze-drying, and is based on obtaining sulfonated chitosan that meets the purity requirements. Among them, in order to facilitate the understanding and implementation of the technical solution of the present application, it is preferred to dialyze in a dialysate with a pH of 6.5-7 for 5-7 days, and the ratio of the volume of the dialysate to the volume of the dialysis solution is about 100.

[0054] According to the lithium-sulfur battery positive electrode material disclosed in the present application, the conductive agent comprises: 0-50% by mass of a first conductive agent and 50-100% by mass of a second conductive agent, wherein the first conductive agent comprises conductive carbon black; and the second conductive agent comprises any one of carboxylated carbon nanotubes, carboxylated graphene, carboxylated conductive carbon black or carboxylated conductive polymers. The present application does not specifically limit the specific source or preparation of the carboxylated carbon nanotubes, carboxylated graphene, carboxylated conductive carbon black or carboxylated conductive polymers, and they can be obtained from commercial sources or synthesized by known carboxyl functionalization methods.

[0055] It should be noted that the present application carboxylates the conductive agent so that the mixed system containing the sulfur positive electrode active material, the conductive agent and the zwitterionic polymer can self-assemble to form a composite positive electrode system driven by inherent multiple interactions rich in ions and hydrogen bonds, thereby effectively improving the stability of the prepared composite positive electrode system.

[0056] According to the lithium-sulfur battery positive electrode material disclosed in the present application, the sulfur positive electrode active substance refers to various sulfur-containing active materials commonly used in the sulfur positive electrode of the sulfur-lithium battery, and may be preferably elemental sulfur, sulfur-based conductive polymers and combinations thereof.

[0057] According to the lithium-sulfur battery positive electrode material disclosed in the present application, the mass percentage content of the sulfur positive electrode active material, the conductive agent and the adaptive binder in the lithium-sulfur battery positive electrode material (the sum of the mass of each component is 100%) is: 60-80 mass% of the sulfur positive electrode active material, 10-38 mass% of the conductive agent, and 2-10 mass% of the adaptive binder. Specifically, the mass percentage content of each component in the lithium-sulfur battery positive electrode material is:

[0058] 80% by mass of sulfur positive electrode active material, 15% by mass of conductive agent and 5% by mass of adaptive binder;

[0059] or

[0060] 70% by mass of sulfur positive electrode active material, 25% by mass of conductive agent and 5% by mass of adaptive binder;

[0061] or

[0062] 65 mass % of sulfur positive electrode active material, 30 mass % of conductive agent and 5 mass % of adaptive binder.

[0063] In a second aspect, an embodiment of the present application provides a lithium-sulfur battery positive electrode sheet, which comprises a plate carrier and an active layer coated on the plate carrier;

[0064] The active layer comprises the lithium-sulfur battery positive electrode material described in the present application.

[0065] Among them, the active layer of the lithium-sulfur battery positive electrode sheet provided in the embodiment of the present application is composed of the lithium-sulfur battery positive electrode material described in the present application, based on the lithium-sulfur battery positive electrode material described above having the ability to resist lithium polysulfide (Li2S x ) Neutral molecules and S x - The anion has an efficient adsorption effect and improves the structural stability of the positive electrode sheet. Therefore, the lithium-sulfur battery positive electrode sheet of the embodiment of the present application has a high sulfur utilization rate and excellent rate performance.

[0066] According to the lithium-sulfur battery positive electrode sheet disclosed in the present application, the electrode sheet carrier is preferably a carbon aluminum foil current collector or a carbon cloth. The specific sources and models of the carbon aluminum foil current collector and the carbon cloth are not particularly limited in the present application embodiment, and various known carbon aluminum foil current collectors and carbon cloths available for lithium-sulfur batteries can be used.

[0067] In a third aspect, the present application also provides a method for preparing the lithium-sulfur battery positive electrode sheet, which preferably comprises the following steps:

[0068] Providing a dispersion containing a sulfur positive electrode active material and a conductive agent;

[0069] Adding an adaptive binder to the dispersion and mixing well to obtain a sulfur positive electrode slurry;

[0070] The sulfur positive electrode slurry is coated on a pole piece carrier and dried to obtain a lithium-sulfur battery positive electrode piece.

[0071] In a fourth aspect, the present application provides a lithium-sulfur battery, the main components of which include the lithium-sulfur battery positive electrode sheet described in the above application, as well as a lithium negative electrode sheet and an electrolyte that can be used in a sulfur-lithium battery. The present application has no special restrictions on the electrolyte, and it can be a common sulfur-lithium battery electrolyte known in the art. At the same time, the present application has no special restrictions on the specific battery type, and it can be a button battery commonly used in the art.

[0072] In the fifth aspect, the embodiment of the present application also provides an electrical device, whose power system includes the lithium-sulfur battery described in the present application. Among them, the present application does not specifically limit the specific type, model and use of the electrical device, which can be various known devices with energy storage characteristics such as electric vehicles and portable electronic devices. The example portable electronic devices include but are not limited to wearable devices such as smart watches, smart wristbands, smart clothing, smart helmets, AR glasses, and portable electronic devices such as mobile phones, laptops, tablets, e-books, and electronic game consoles.

[0073] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0074] Example 1

[0075] This example provides a preparation method of sulfonated chitosan (SCS-30%), the steps comprising:

[0076] After 1g of chitosan was swollen in 50mL of deionized water and stirred for 1h, 600μL of 1,3-propane sultone was slowly added and reacted at 30℃ for 4h. The product was purified by dialysis for 7 days, wherein the pH of the dialysate was 6.5, the dialysate was changed 3 times a day in the first 3 days, and 2 times a day in the remaining 4 days, and the volume of the dialysate was controlled to be 100 with the volume of the dialysate solution. Finally, sulfonated chitosan (SCS-30%) was separated from the solution by freeze drying.

[0077] According to the method described above, the amount of 1,3-propane sultone added was adjusted to 800 μL and 1000 μL, respectively, to obtain sulfonated chitosan (SCS-40%) and sulfonated chitosan (SCS-50%).

[0078] To illustrate the successful synthesis of sulfonated chitosan, the three sulfonated chitosan products prepared in Example 1 were characterized by infrared spectroscopy. Figure 1 As shown. Among them, Figure 1 This is the infrared spectrum of the sulfonated chitosan product prepared in Example 1.

[0079] according to Figure 1 It can be seen that the present invention successfully synthesized sulfonated chitosan by adding different volumes of 1,3-propane sultone, and sulfonated chitosan with different sulfonation degrees can be prepared by adding different volumes of 1,3-propane sultone, indicating that the sulfonation degree of the prepared sulfonated chitosan can be regulated by controlling the amount of 1,3-propane sultone added.

[0080] Furthermore, the sulfonation degree of the sulfonated chitosan prepared in the above-mentioned embodiment was determined by elemental analysis test, and the results are shown in Table 1.

[0081] Table 1: Elemental analysis test results

[0082]

[0083] According to Table 1, after adding 600 μL, 800 μL and 1000 μL of 1,3-propane sultone (sulfonation reagent) to the chitosan aqueous solution, sulfonated chitosan with different sulfonation degrees was prepared, which further confirmed that the sulfonation degree of sulfonated chitosan can be effectively regulated by controlling the amount of sulfonation reagent added.

[0084] Example 2

[0085] This embodiment provides the preparation of a lithium-sulfur battery positive electrode sheet (LSBs-PP1). Wherein, taking the total mass of the lithium-sulfur battery positive electrode material as 100%, the material composition is:

[0086] Elemental sulfur 80%;

[0087] Carboxylated carbon nanotubes 15%;

[0088] Sulfonated chitosan 5%;

[0089] The specific preparation steps include:

[0090] S1: 0.1 g of sulfonated chitosan (SCS-50%) was fully swollen in 8 mL of deionized water to obtain an adhesive solution for use;

[0091] S2: After ball-milling the carboxylated carbon nanotubes and elemental sulfur for 2 hours, the binder solution was added and the ball-milling was continued for 6 hours to obtain an active slurry, wherein the ball-milling speed was 600 rpm;

[0092] S3: The active slurry is scraped onto a carbon-coated aluminum foil with a scraper thickness of 150 μm, and then dried in a vacuum oven at 40° C. for 4 h and 40° C. for 8 h to obtain a lithium-sulfur battery positive electrode sheet (LSBs-PP1).

[0093] In order to test the actual performance of the lithium-sulfur battery cathode prepared in this application, the cathode LSBs-PP1 and the lithium metal anode were assembled into a Li-S button full battery and the electrochemical performance was tested, wherein the electrolyte composition was a mixture of 1,3-pentylene oxide (DOL) and tetraethylene glycol dimethyl ether (DME) in a volume ratio of 1:1, and 1M lithium bis(trifluoromethylsulfonyl)imide and 1wt% anhydrous lithium nitrate were dissolved in the mixture. The specific test method includes:

[0094] The LAND battery charge and discharge instrument was used to test the charge, discharge and cycle performance of the Li-S button battery. The charge and discharge range was 1.7V-2.8V, and the charge and discharge was performed at a current density of 4C. Figure 2 The discharge curve and coulomb efficiency test diagram of the Li-S full battery made based on the positive electrode LSBs-PP1 (based on the fact that the Li-S full battery can be charged and discharged relatively stably).

[0095] according to Figure 2 It can be seen that after 700 cycles of the Li-S button battery at 4C, the capacity retention rate is 62.5%, indicating that the positive electrode sheet LSBs-PP1 has good electrochemical cycling performance.

[0096] This paper also explores the effect of sulfonation degree on the performance of lithium-sulfur battery positive electrode sheets. Specifically, according to the material composition and dosage described in Example 2, lithium-sulfur battery positive electrode sheets containing sulfonated chitosan with different sulfonation degrees were prepared, and the prepared lithium-sulfur battery positive electrode sheets were assembled into Li-S button full batteries. The specific capacity-voltage of each Li-S button full battery was tested, and the results were as follows: Figure 3 shown.

[0097] according to Figure 3 It can be seen that when the addition amount of sulfonated chitosan is the same, the discharge capacity of the Li-S button full battery assembled based on SCS-40% sulfonated chitosan at 0.1C and 1C is the largest, indicating that 40% sulfonation degree is the best.

[0098] This paper also explores the effect of the amount of sulfonated chitosan added on the performance of the lithium-sulfur battery positive electrode. Specifically, according to Example 2, lithium-sulfur battery positive electrodes containing different amounts of sulfonated chitosan (SCS-40%) were prepared, and the prepared lithium-sulfur battery positive electrodes were assembled into Li-S button full batteries. The charge, discharge and cycle performance of each Li-S button full battery was tested, and the results are described in Table 2.

[0099] Table 2: Electrochemical performance at different addition amounts of sulfonated chitosan

[0100]

[0101]

[0102] According to Table 2, the discharge capacity of the Li-S button cell decreases with the increase of the amount of sulfonated chitosan added, so the preferred amount of sulfonated chitosan added is preferably 2-10wt%, more preferably 2-5wt%.

[0103] Example 3

[0104] This embodiment provides the preparation of a lithium-sulfur battery positive electrode sheet (LSBs-PP2). Wherein, taking the total mass of the lithium-sulfur battery positive electrode material as 100%, the material composition is:

[0105]

[0106] The specific preparation steps include:

[0107] S1: 0.1 g of sulfonated chitosan (SCS-50%) was fully swollen in 8 mL of deionized water to obtain an adhesive solution for use;

[0108] S2: After ball-milling the carboxylated carbon nanotubes, Super P Li and elemental sulfur for 2 hours, the binder solution was added and the ball-milling was continued for 6 hours to obtain an active slurry, wherein the ball-milling speed was 600 rpm;

[0109] S3: The active slurry is scraped onto a carbon-coated aluminum foil with a scraper thickness of 150 μm, and then dried at 40° C. for 4 h and in a vacuum oven at 40° C. for 8 h to obtain a lithium-sulfur battery positive electrode sheet (LSBs-PP2).

[0110] The surface structure of the positive electrode of the lithium-sulfur battery was characterized using a scanning electron microscope. Figure 4 As shown. Among them, Figure 4 This is the surface SEM image of the lithium-sulfur battery positive electrode LSBs-PP2.

[0111] according to Figure 4 It can be seen that the elemental sulfur particles are properly dispersed in the conductive network of the entire cathode sheet, maximizing the exposure of active elemental sulfur, which is beneficial to improve electrolyte contact, reduce resistance and provide a shorter Li + Migration path.

[0112] Example 4

[0113] This embodiment provides the preparation of a lithium-sulfur battery positive electrode sheet (LSBs-PP3). Wherein, taking the total mass of the lithium-sulfur battery positive electrode material as 100%, the material composition is:

[0114]

[0115] The specific preparation steps include:

[0116] S1: 0.1 g of sulfonated chitosan (SCS-50%) was fully swollen in 8 mL of deionized water to obtain an adhesive solution for use;

[0117] S2: After ball-milling the carboxylated carbon nanotubes and elemental sulfur for 2 hours, the binder solution was added and the ball-milling was continued for 6 hours to obtain an active slurry, wherein the ball-milling speed was 600 rpm;

[0118] S3: The active slurry is scraped onto a carbon-coated aluminum foil with a scraper thickness of 150 μm, and then dried at 40° C. for 4 h and in a vacuum oven at 40° C. for 8 h to obtain a lithium-sulfur battery positive electrode sheet (LSBs-PP3).

[0119] Example 5

[0120] This embodiment provides a lithium-sulfur soft pack battery, comprising:

[0121] Lithium sulfur battery cathode (LSBs-PP2), with a loading of 6 mg / cm 2 , size is 6 cm×5 cm, the lithium strip size is 6.5cm×5.5 cm, and the thickness is 0.1 mm.

[0122] The aluminum tab was bonded to the positive electrode, the nickel tab was bonded to the lithium negative electrode, 100 μL of electrolyte (a mixed solution of 1,3-pentylene oxide (DOL) and tetraethylene glycol dimethyl ether (DME) with a volume ratio of 1:1, and the mixed solution contained 1M lithium bis(trifluoromethylsulfonyl)imide and 1wt% anhydrous lithium nitrate), and then sealed after standing for 1 hour under vacuum. The entire soft pack battery assembly process was completed in a glove box (<0.1 ppm H2O and <0.1ppm O2).

[0123] Finally, the battery performance was tested as follows: The battery cycle performance was tested using a LAND battery charge and discharge instrument, with a charge and discharge range of 1.7V-2.8V and a current density of 0.1C. The results were Figures 5 and 6 As shown. Among them, Figure 5 This is the 0.1C cycle performance diagram of Li-S soft pack battery; Figure 6 This is a lighting diagram of the Li-S soft pack battery.

[0124] according to Figure 5 It can be seen that the Li-S soft pack battery has a capacity of nearly 10 mAh / cm at a rate of 0.1C. 2The surface capacity of the battery is 20 cycles, and the capacity is almost not decayed, which shows that the positive electrode sheet of the lithium-sulfur battery of the present application has good stability.

[0125] according to Figure 6 It can be seen that the lamp powered by the lithium-sulfur soft-pack battery was successfully lit, indicating that the assembled soft-pack battery can work normally.

[0126] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0127] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A lithium-sulfur battery positive electrode material, characterized in that: The raw materials include: Sulfur cathode active material; a conductive agent; and, Adaptive adhesives; Wherein, the adaptive adhesive is a zwitterionic polymer.

2. The lithium-sulfur battery positive electrode material according to claim 1, characterized in that The zwitterionic polymer comprises sulfonated chitosan or sulfonated polyethyleneimine.

3. The lithium-sulfur battery positive electrode material according to claim 1, characterized in that: The conductive agent comprises 0-50 mass % of a first conductive agent and 50-100 mass % of a second conductive agent; The first conductive agent is conductive carbon black; The second conductive agent includes any one of carboxylated carbon nanotubes, carboxylated graphene, carboxylated conductive carbon black, or carboxylated conductive polymers.

4. The lithium-sulfur battery positive electrode material according to claim 1, characterized in that The sulfur positive electrode active material includes elemental sulfur or a sulfur-based conductive polymer.

5. The lithium-sulfur battery positive electrode material according to any one of claims 1 to 4, characterized in that: Include: 60-80% by mass of sulfur positive electrode active material; 10-38% by mass of conductive agent; and, 2-10 mass % of an adaptive binder.

6. A lithium-sulfur battery positive electrode sheet, characterized in that: Include: a pole piece carrier; and An active layer coated on the pole piece carrier; The active layer comprises the lithium-sulfur battery positive electrode material according to any one of claims 1-5.

7. The lithium-sulfur battery positive electrode sheet according to claim 6, characterized in that: The pole piece carrier comprises a carbon aluminum foil current collector or a carbon cloth.

8. A method for preparing a lithium-sulfur battery positive electrode sheet according to claim 6 or 7, characterized in that: Contains steps: Providing a dispersion containing a sulfur positive electrode active material and a conductive agent; Adding an adaptive binder to the dispersion and mixing well to obtain a sulfur positive electrode slurry; The sulfur positive electrode slurry is coated on a pole piece carrier and dried to obtain a lithium-sulfur battery positive electrode piece.

9. A lithium-sulfur battery, characterized in that: A lithium-sulfur battery positive electrode sheet comprising the positive electrode sheet of claim 6 or 7.

10. An electrical equipment, characterized in that: A lithium-sulfur battery comprising the lithium-sulfur battery according to claim 9.